Another suggestion regarding the etymology of the Hebrew noun mērēaʻ - Lemardelé, Christophe (2012)
The Hebrew noun mērēa‘ is not isolated. Saul M. Olyan connects it with the verbs r‘h and, more speculatively, with a rare meaning of r‘‘. His suggestion is correct because the meaning of “companion” is figurative in the context of the development of the biconsonantal root r‘. Following the theory of the French linguist Georges Bohas, I propose to understand this development with the concepts of “etymon” and “matrix”.
Das hebräische Nomen mērēa‘ ist nicht isoliert. Saul M. Olyan verbindet es mit dem Verb r‘h und, mehr spekulativ, mit einer seltenen Bedeutung von r‘‘. Er hat recht, denn die Bedeutung „Kumpan“ ist im Zusammenhang der Entwicklung der zweikonsonantischen Wurzel r‘ als bildlich zu beurteilen. Im Anschluss an die Theorie des französischen Linguisten Georges Bohas schlage ich vor, diese Entwicklung mit den Begriff „Etymon“ und „Matrix“ zu erklären.